2016
DOI: 10.1038/srep38909
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Neurological Outcome within 72 h after Traumatic Cervical Spinal Cord Injury

Abstract: To investigate the prognostic values of clinical factors 72 h within traumatic cervical spinal cord injury (TCSCI). Data were extracted from the medical materials of 57 TCSCI cases. AIS was used as the outcome measure and divided into dichotomous variables by two methods, i.e. “complete(AIS = A)/incomplete(AIS ≠ A) SCI” and “motor complete(AIS = A or B)/incomplete(AIS ≠ A and B) SCI”. Relationships between evaluated factors and outcomes were investigated by univariate and multivariate methods. MRI Cord transec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
(29 reference statements)
1
12
0
3
Order By: Relevance
“…It was recognized that either primary or secondary injury was associated with the outcome of tSCI patients was considered to be [ 4 , 5 ], and several standard prognostic factors at admission, including age, blood cells counts, coagulation status, Charleson Co-morbidity Index (CCI), American spinal injury association Impairment Scale (AIS) grades, and the initial Glasgow Coma Scale (GCS) score, were identified to be associated with the outcome of tSCI patients [ 6 , 7 ]; however, their prognostic values were limited even a variety of predictive models were built. Thus, to develop a model with higher prognostic value is justified.…”
Section: Introductionmentioning
confidence: 99%
“…It was recognized that either primary or secondary injury was associated with the outcome of tSCI patients was considered to be [ 4 , 5 ], and several standard prognostic factors at admission, including age, blood cells counts, coagulation status, Charleson Co-morbidity Index (CCI), American spinal injury association Impairment Scale (AIS) grades, and the initial Glasgow Coma Scale (GCS) score, were identified to be associated with the outcome of tSCI patients [ 6 , 7 ]; however, their prognostic values were limited even a variety of predictive models were built. Thus, to develop a model with higher prognostic value is justified.…”
Section: Introductionmentioning
confidence: 99%
“…Qiu et al . [18] showed that all the cases with cord transection showed complete SCIs without neurological recovery. Cord transection should be the best predictors for complete SCI.…”
Section: Discussionmentioning
confidence: 99%
“…On sagittal T 2 images, normal cord shows no signal abnormalities and oedema shows high signal intensity, while acute haemorrhage elicits hypointense signal with a thin rim of high signal intensity. 5…”
Section: Learning Pointsmentioning
confidence: 99%
“…Contusion shows normal images on T 1 WI, while the spinal cord on T 2 WI elicits a small central area of abnormal signal intensity. 5…”
Section: Learning Pointsmentioning
confidence: 99%